2014
DOI: 10.1093/mnras/stu1523
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evolution of dim isolated neutron stars

Abstract: The dim isolated neutron stars (XDINs) have periods in the same range as the anomalous X-ray pulsars (AXPs) and the soft gamma-ray repeaters (SGRs). We apply the fallback disk model, which explains the period clustering and other properties of AXP/SGRs, to the six XDINs with measured periods and period derivatives. Present properties of XDINs are obtained in evolutionary scenarios with surface dipole magnetic fields B 0 ∼ 10 12 G. The XDINs have gone through an accretion epoch with rapid spin-down earlier, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(70 citation statements)
references
References 69 publications
(86 reference statements)
5
65
0
Order By: Relevance
“…There are three basic disc parameters that are expected to be similar for the fallback discs of different systems: the X-ray irradiation efficiency (C), the minimum critical temperature below which the disc becomes viscously passive (T p ), and the α parameter of the kinematic viscosity (Shakura and Sunyaev, 1973). In this work, we use the same values of the C, T p , and α parameters as those employed earlier in the evolution models of individual AXP/SGRs (Benli and Ertan, 2016), XDINs (Ertan et al, 2014), and the three HBRPs with measured braking indices (Benli and Ertan, 2017).…”
Section: Model Parametersmentioning
confidence: 99%
“…There are three basic disc parameters that are expected to be similar for the fallback discs of different systems: the X-ray irradiation efficiency (C), the minimum critical temperature below which the disc becomes viscously passive (T p ), and the α parameter of the kinematic viscosity (Shakura and Sunyaev, 1973). In this work, we use the same values of the C, T p , and α parameters as those employed earlier in the evolution models of individual AXP/SGRs (Benli and Ertan, 2016), XDINs (Ertan et al, 2014), and the three HBRPs with measured braking indices (Benli and Ertan, 2017).…”
Section: Model Parametersmentioning
confidence: 99%
“…Considering alternatively an active fallback disk model, Ertan et al (2017Ertan et al ( , 2014 showed that such a disk is able to produce the X-ray properties and the optical excess of the XTINSs. Here, we use their model to check whether such a fallback disk can reproduce the measured NIR excess.…”
Section: Emission From Circumstellar Material?mentioning
confidence: 99%
“…The model also considers X-ray irradiation which is most relevant for the passive outer part of the disk. For details on the model and the model parameters for RX J0806.4-4123, we refer to Ertan et al (2017Ertan et al ( , 2014. The outer radius of the passive disk is not well known and depends on the initial disk conditions and the Xray luminosity in the early phase of evolution.…”
Section: Emission From Circumstellar Material?mentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that XDINSs are supposed to be dead magnetars. In addition to these, two magnetars may have passive fallback disks (Wang et al 2006;Ertan et al (2014) interpret that XDINSs have gone through a past accretion phase with spin-down and emerged in their current state. In Figure 5, we could find that the radio-loud magnetars are above the death line.…”
Section: Discussionmentioning
confidence: 99%